2013
DOI: 10.1002/ente.201300087
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of an Air‐to‐Water Heat Pump System to Evaluate the Impact of Demand‐Side‐Management Measures on Efficiency and Load‐Shifting Potential

Abstract: Increasing variable renewable electricity generation in Germany challenges the German electricity supply in terms of mismatch between supply and demand as well as grid stability. Demand side management (DSM), a portfolio of measures to improve the energy system on the consumption side, can contribute to the ability to cope with the upcoming challenges in the future smart power grid.1 Currently, over 500 000 electrical compression heat pumps (HP) provide a potential for DSM in Germany.2, 3, 4 Whereas static loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 9 publications
0
30
0
Order By: Relevance
“…A heat pump with seven borehole heat exchanger, each one with 125 meters of depth, heated water to 40°C. Both the research in Portugal and that conducted by the Fraunhofer Institute for Solar Energy Systems ISE [13] show that heating systems with ground sources heat pumps achieve similar results.…”
Section: Heating System Operation -Results Of Researchmentioning
confidence: 69%
“…A heat pump with seven borehole heat exchanger, each one with 125 meters of depth, heated water to 40°C. Both the research in Portugal and that conducted by the Fraunhofer Institute for Solar Energy Systems ISE [13] show that heating systems with ground sources heat pumps achieve similar results.…”
Section: Heating System Operation -Results Of Researchmentioning
confidence: 69%
“…In this paper, the proposed control strategy has demonstrated that efficient load shifting is possible when applying a time-varying price structure. If this price profile is designed in a smart manner, the periods of cheaper energy price could coincide with periods of high production of RES, for instance [39]. In this way, the goal of cost savings would go along with an improvement in RES consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Variable COPs used in Equation (3) are also applied in this energy cost calculation, and a similar equation is obtained for electricity consumptions by heat pumps as shown in Equation (7). Such a calculation method has also been used in other studies [28,29].…”
Section: Energy Costmentioning
confidence: 99%